Assessing Punitive and Cooperative Strategies of Corporate Crime Control for Select Companies Operating in 1995 Through 2000 (United States) - Simpson, Sally S. ([Verlag nicht ermittelbar], 2011)
The purpose of the study was to evaluate the extent to which deterrence or cooperative strategies motivated firms and their facilities to comply with environmental regulations. The project collected administrative data (secondary data) for a sample of publicly owned, United States companies in the pulp and paper, steel, and oil refining industries from 1995 to 2000 to track each firm's economic, environmental, and enforcement compliance history. Company Economic and Size Data (Part 1) from 1993 to 2000 were gathered from the Standard and Poor's Industrial Compustat, Mergent Online, and Securities and Exchange Commission, resulting in 512 company/year observations. Next, the research team used the Directory of Corporate Affiliations, the Environmental Protection Agency's (EPA) Toxic Release Inventory (TRI), and the EPA's Permit Compliance System (PCS) to identify all facilities owned by the sample of firms between 1995 and 2000. Researchers then gathered Facility Ownership Data (Part 2), resulting in 15,408 facility/year observations. The research team gathered various types of PCS data from the EPA for facilities in the sample. Permit Compliance System Facility Data (Part 3) were gathered on the 214 unique major National Pollutant Discharge Elimination System (NPDES) permits issued to facilities in the sample. Although permits were given to facilities, facilities could have one or more discharge points (e.g., pipes) that released polluted water directly into surface waters. Thus, Permit Compliance System Discharge Points (Pipe Layout) Data (Part 4) were also collected on 1,995 pipes. The EPA determined compliance using two methods: inspections and evaluations/assessments. Permit Compliance System Inspections Data (Part 5) were collected on a total of 1,943 inspections. Permit Compliance System Compliance Schedule Data (Part 6) were collected on a total of 3,336 compliance schedule events. Permit Compliance System Compliance Schedule Violation Data (Part 7) were obtained for a total of 246 compliance schedule violations. Permit Compliance System Single Event Violations Data (Part 8) were collected on 75 single event violations. Permit Compliance System Measurement/Effluent and Reporting Violations Data (Part 9) were collected for 396,479 violations. Permit Compliance System Enforcement Actions Data (Part 10) were collected on 1,730 enforcement actions. Occupational Safety and Health Administration Data (Part 11) were collected on a total of 2,243 inspections. The OSHA data were collected by company name and include multiple facilities owned by each company and were not limited to facilities in the Permit Compliance System. Additional information about firm noncompliance was drawn from EPA Docket and CrimDoc systems. Administrative and Judicial Docket Case Data (Part 12) were collected on 40 administrative and civil cases. Administrative and Judicial Docket Case Settlement Data (Part 13) were collected on 36 administrative and civil cases. Criminal Case Data (Part 14) were collected on three criminal cases. For secondary data analysis purposes, the research team created the Yearly Final Report Data (Part 15) and the Quarterly Final Report Data (Part 16). The yearly data contain a total of 378 company/year observations; the quarterly data contain a total of 1,486 company/quarter observations. The research team also conducted a vignette survey of the same set of companies that are in the secondary data to measure compliance and managerial decision-making. Concerning the Vignette Data (Part 17), a factorial survey was developed and administered to company managers tapping into perceptions of the costs and benefits of pro-social and anti-social conduct for themselves and their companies. A total of 114 respondents from 2 of the sampled corporations read and responded to a total of 384 vignettes representing 4 scenario types: technical noncompliance, significant noncompliance, over-compliance, and response to counter-terrorism. Part 1 contains 19 economic and size variables. Part 2 contains a total of eight variables relating to ownership. Part 3 contains 67 variables with regard to facility characteristics. Part 4 contains 31 variables relating to discharge points and pipe layout information. Part 5 contains 13 inspections characteristics variables. Part 6 contains 13 compliance schedule event characteristics variables. Part 7 contains 11 compliance schedule violation characteristics variables. Part 8 contains 10 single event violation characteristics variables. Part 9 contains 79 variables including variables for matching limits and discharge monitoring reports, actual limits (permitted levels) variables, standardized limits variables, statistical base codes variables, reported units on limits variables, units for standardized limits variables, sampling information variables, additional limits information, actual DMR reports for each limit, effluent violations, and variables relating to technical aspects of reporting. Part 10 contains 26 enforcement actions variables. Part 11 contains 24 Occupational Safety and Health Administration inspection variables. Part 12 contains 39 administrative and judicial court case characteristics variables. Part 13 contains 21 court case settlement characteristics variables. Part 14 contains 9 criminal case characteristics variables. Part 15 contains 95 variables created for final report analyses by year. Part 16 contains 46 variables created for final report analyses by quarter. Part 17 contains 157 variables including pro-social variables with security/over-compliance intentions, noncompliance variables with technical/significant noncompliance intentions, vignette characteristics variables, other variables derived from survey questions, environmental norms variables, and demographic characteristics variables.